Sexual Crime and Prevention (Sexual Crime, 2018)
This book brings together a thought-provoking collection of original contributions to the study of sexual crime prevention. Written in an accessible and practical style, the book begins with an exploration of the theoretical underpinnings of sexual crime prevention, as well as the history and development of prevention work over the years, providing an overview of prevention initiatives around the world. The second section spotlights three in depth case studies of organisations delivering prevention work in the UK. Final sections of the book explore the service user experience, impact of the media, and attitudes and consideration of future directions for prevention work. The book is relevant not only to psychologists, criminologists, social workers and students, but to practitioners, researchers and anyone with an interest in learning about sexual crime prevention. Rebecca Lievesley is a Lecturer in Psychology at Nottingham Trent University and has conducted research within the criminal justice system for many years. She is also a co-founder and Trustee of the Safer Living Foundation. Kerensa Hocken is a registered forensic psychologist at HMPPS Whatton, UK. She has oversight for the assessment and treatment of people in prison for sexual offending in the Midlands region. Helen Elliott is Lecturer in Counselling at Bishop Grosseteste University, UK. She has a background in forensic psychology and is a trainee integrative psychotherapist. Belinda Winder is Head of the Sexual Offences, Crime and Misconduct Research Unit at Nottingham Trent University, UK. Nicholas Blagden is a Senior Lecturer in Forensic Psychology. He is a Chartered Psychologist and has worked and researched within the criminal justice system and HM Prison Service for many years. Phil Banyard is Associate in Psychology at Nottingham Trent University, UK. He was recently honoured with the British Psychological Society's Award for Distinguished Contributions to Psychology Education.